Conflicts in the Franchise Industry: How to Forge a Win-Win Partnership - Jinkook Lee (Korea Development Institute (KDI), 2019)
Korea's franchise market is wavering. Amid the heavy concentration of food service businesses and the high number of inexperienced franchisors, franchisees have had little opportunity to grow. Moreover, the terms and conditions of franchise agreements have become a source of contention due to their contradicting impact on the performances of franchisors and franchisees. Accordingly, government efforts are needed to overhaul information disclosure documents so that they accurately reflect the information and data on, for example, the franchisor's experience and background, and the franchise store's average sales figures, etc. At the same time, the fixed-percentage royalty should be promoted through discussions with respective industries and guidelines established for essential items. Actions must include exploring temporary measures to strengthen the qualifications for franchise businesses, particularly in sectors that show a high concentration of certain businesses.
Keywords: 330